2017
DOI: 10.1007/s00277-017-2994-x
|View full text |Cite
|
Sign up to set email alerts
|

Ruxolitinib reduces JAK2 p.V617F allele burden in patients with polycythemia vera enrolled in the RESPONSE study

Abstract: In patients with polycythemia vera (PV), an elevated JAK2 p.V617F allele burden is associated with indicators of more severe disease (e.g., leukocytosis, splenomegaly, and increased thrombosis risk); however, correlations between allele burden reductions and clinical benefit in patients with PV have not been extensively evaluated in a randomized trial. This exploratory analysis from the multicenter, open-label, phase 3 Randomized Study of Efficacy and Safety in Polycythemia Vera With JAK Inhibitor INCB018424 V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 15 publications
(13 reference statements)
2
74
1
1
Order By: Relevance
“…Thromboembolic events were more frequent in the BAT arm but this was not a pre‐determined outcome. Data published from this study also suggested that molecular responses can occur, perhaps to the same extent as with IFN (Pieri et al , ; Vannucchi et al , ) and that even profoundly iron deficient patients can normalise their iron parameters with ruxolitinib therapy (Verstovsek et al , ). Disease transformation occurred and there is no information to suggest that ruxolitinib therapy impacts these events.…”
Section: Cytoreductive Therapymentioning
confidence: 56%
“…Thromboembolic events were more frequent in the BAT arm but this was not a pre‐determined outcome. Data published from this study also suggested that molecular responses can occur, perhaps to the same extent as with IFN (Pieri et al , ; Vannucchi et al , ) and that even profoundly iron deficient patients can normalise their iron parameters with ruxolitinib therapy (Verstovsek et al , ). Disease transformation occurred and there is no information to suggest that ruxolitinib therapy impacts these events.…”
Section: Cytoreductive Therapymentioning
confidence: 56%
“…(44) Longer term follow-up of the RESPONSE trial has shown a steady decrease in the JAK2 V617F allele burden among patients originally randomized to ruxolitinib (22% mean reduction at weak 80, 40% by week 208). (96, 97) While the significance of JAK2 V617F allele burden reduction in MPN remains unknown, these findings underscore the fact that this action is not unique to HDACI. Finally, given the success of pegylated interferon alfa-2a in PV,(98, 99) a longer acting interferon, ropeginterferon alfa-2b, which allows administration every 2 weeks, has been developed.…”
Section: Expert Opinionmentioning
confidence: 88%
“…29 The mean percent change from baseline JAK2 V617F allele burden among the 104 patients randomized to ruxolitinib was −40% at week 208. 30 …”
Section: Developmental Therapeutics In Pv and Etmentioning
confidence: 99%